Who Is in Justice? Caste, Religion and Gender in the Courts of Bihar over a Decade - Bhupatiraju, Sandeep; Chen, Daniel L.; Joshi, Shareen; Neis, Peter (World Bank, Washington, DC, 2021)
Bihar is widely regarded as one of India’s poorest and most divided states. It has also been the site of many social movements that have left indelible marks on the state’s politics and identity. Little is currently known about how structural inequalities have affected the functioning of formal systems of justice in the state. This paper uses a novel dataset of more than one million cases filed at the Patna high court between 2009 and 2019 together with a variety of supplementary data to analyze the role of religion, caste and gender in the high court of Bihar. The analysis finds that the courts are not representative of the Bihari population. Muslims, women and scheduled castes are consistently under-represented. The practice of using “caste neutral” names is on the rise. Though there is little evidence of “matching” between judges and petitioners or judges and filing advocates on the basis of names, there is evidence that petitioners and their advocates match on the basis of identity such as the use of “caste neutral” names. These results suggest that the social movements that disrupted existing social structures in the past may have inadvertently created new social categories that reinforce networks and inequalities in the formal justice system.